Respostas
respondido por:
1
Olá!!
Resolução!!!
a)
= 4x ( - 6x + 8 )
= - 24x² + 32x²
= 8x²
b)
= 6x ( - 7 - 2 )
= - 42x - 42x
= - 84x
c)
= 3x ( - 9x + 4x )
= - 27x² + 12x²
= - 15x²
d)
= a ( - a + b )
= - a² + ab
Espero ter ajudado!!
Resolução!!!
a)
= 4x ( - 6x + 8 )
= - 24x² + 32x²
= 8x²
b)
= 6x ( - 7 - 2 )
= - 42x - 42x
= - 84x
c)
= 3x ( - 9x + 4x )
= - 27x² + 12x²
= - 15x²
d)
= a ( - a + b )
= - a² + ab
Espero ter ajudado!!
Brunogamer322:
Vlw man
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás